The Effect of Transformational Leadership on the Quality of Nurses' Interprofessional Collaboration in Inpatient Wards - Syahrir Aprizal; Muhammad Hadi; Naryati Naryati; Harif Fadhlillah (Indonesian Journal of Global Health Research, 2026)
The quality of healthcare services is influenced by healthcare workers' ability to perform effective interprofessional collaboration (IPC). Transformational leadership of head nurses plays an important role in improving communication, coordination, and teamwork among healthcare professionals in inpatient wards. This study aimed to analyze the effect of transformational leadership of head nurses on the quality of interprofessional collaboration among staff nurses in hospital inpatient wards. This study used a quasi-experimental design with a non-equivalent control group design. The sample consisted of 50 respondents, including 25 participants in the intervention group and 25 in the control group selected using purposive sampling. The intervention group received supervision and transformational leadership reinforcement for one month. The instruments used were transformational leadership and PINCOM-Q questionnaires, which were valid and reliable with Cronbach's Alpha values of 0.912 and 0.894, respectively. The data were analyzed using General Linear Model Repeated Measure (GLM-RM). The mean transformational leadership score in the intervention group increased from 139.84 to 179.64, while the control group remained relatively stable. Multivariate analysis showed a significant difference in the intervention group (p=0.002; Partial Eta Squared=0.349). The mean IPC score in the intervention group increased from 62.56 to 71.80 with significant results (p=0.010; Partial Eta Squared=0.281). GLM-RM analysis demonstrated a significant effect of the intervention on transformational leadership (F=120.745; p<0.001) and IPC (F=7.543; p=0.008). Supervision and transformational leadership reinforcement were effective in improving transformational leadership among head nurses and the quality of interprofessional collaboration among staff nurses in hospital inpatient wards.